2016
DOI: 10.2138/am-2016-5572
|View full text |Cite
|
Sign up to set email alerts
|

Natural Mg-Fe clinochlores: Enthalpies of formation and dehydroxylation derived from calorimetric study

Abstract: This paper presents the results of the first experimental thermochemical investigation of two natural trioctahedral chlorites (clinochlores). The study was performed with the help of a high-temperature heat-flux Tian-Calvet microcalorimeter. The samples were characterized by X-ray spectroscopy analysis, X-ray powder diffraction, thermal analysis, and FTIR spectroscopy. The enthalpies of formation of clinochlores were found using the melt solution calorimetry method to be: -8806 ± 16 kJ/mol for composition (Mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
(24 reference statements)
1
0
0
Order By: Relevance
“…Although the thermal treatment process is essential for the decomposition of the metal precursor, there is a significant change in the catalyst properties caused by heating above 250 o C, which is associated with the loss of water and the collapse of the layered structure. In agreement with previous studies (Hayashi et al, 1969;Kok, 2013;Ogorodova et al, 2016), our TGA-DSC data confirmed the stepwise removal of water from Sep, which accounts for ~9% of the mass loss at 100 o C and ~4% at 250-300 o C (both steps are endothermic processes as expected) with the total mass loss of ~18% by 900 o C ( Figure 5). The exothermic peak observed at o C corresponds to a high temperature phase transition resulting in a complete loss of the Sep structure.…”
Section: Resultssupporting
confidence: 93%
“…Although the thermal treatment process is essential for the decomposition of the metal precursor, there is a significant change in the catalyst properties caused by heating above 250 o C, which is associated with the loss of water and the collapse of the layered structure. In agreement with previous studies (Hayashi et al, 1969;Kok, 2013;Ogorodova et al, 2016), our TGA-DSC data confirmed the stepwise removal of water from Sep, which accounts for ~9% of the mass loss at 100 o C and ~4% at 250-300 o C (both steps are endothermic processes as expected) with the total mass loss of ~18% by 900 o C ( Figure 5). The exothermic peak observed at o C corresponds to a high temperature phase transition resulting in a complete loss of the Sep structure.…”
Section: Resultssupporting
confidence: 93%